Assessing authenticity in modelling test items: deriving a theoretical model - Schlüter, Dominik; Besser, Michael (Frontiers in Education, 2024)
Authenticity is considered a central feature in the context of teaching and learning mathematical modelling and is often demanded for both learning tasks and test items. Although large-scale studies hark back to this construct for years, it is largely unclear how a theoretical and empirically robust model for the description and practical operationalization of authenticity in modelling test items might look like. The article addresses this research desideratum and aims at deriving such a model based on existing theoretical concepts in mathematics education. The article provides a broad theoretical overview of the status quo of the construct and presents the “Model for Authenticity in Modelling Test Items” (MAMTI) as a result of those theoretical considerations. The model is based on the ideas of constructivist object authenticity and comprises a total of 8 aspects: real-world context, events, objects, question/assignment, data, figures, use of mathematics and purpose. The model enables further empirical studies to analyze and classify modelling test items or to vary them in terms of authenticity expression.